PREVENTIVE AND THERAPEUTIC AGENTS FOR SKIN CARE IN PRETERM INFANTS - N.D. Odinaeva; I.A. Belyaeva; G.V. Yatsyk (Педиатрическая фармакология)
Proper care for a baby’s skin is extremely important for the adequate functioning of an infant’s skin and health. Care agents must be selected in accordance with age and purpose of application. In addition, each ingredient contained in a cosmetic or therapeutic agent for external application must be safe. The article describes the experience of leading neonatology physicians in using preventive and therapeutic agents for skin care in newborn infants, including preterm infants.Key words: newborn infants, skin, care.